Infantile epileptic encephalopathy with hypsarrhythmia (infantile spasms/west syndrome) and immunity - Montelli, Terezinha de Cresci Braga [UNESP]; Peraçoli, M. T S [UNESP] (Bentham Science Publishers, 2008)
West syndrome is a severe epilepsy, occurring in infancy, that comprises epileptic seizures known as spasms, in clusters, and a unique EEG pattern, hypsarrhythmia, with psychomotor regression. Maturation of the brain is a crucial component. The onset is within the first year of life, before 12 months of age. Patients are classified as cryptogenic (10 to 20%), when there are no known or diagnosed previous cerebral insults, and symptomatic (80 to 90%), when associated with pre-existing cerebral damages. The time interval from a brain insult to infantile spasms onset ranged from 6 weeks to 11 months. West syndrome has a time-limited natural evolutive course, usually disappearing by 3 or 4 years of age. In 62% of patients, there are transitions to another age-related epileptic encephalopathies, the Lennox-Gastaut Syndrome and severe epilepsy with multiple independent foci. Spontaneous remission and remission after viral infections may occur. Therapy with ACTH and corticosteroids are the most effective. Reports about intravenous immunoglobulins action deserve attention. There is also immune dysfunction, characterized mainly by anergy, impaired cell-mediated immunity, presence of immature thymocytes in peripheral blood, functional impairment of T lymphocytes induced by plasma inhibitory factors, and altered levels of immunoglobulins. Changes in B lymphocytes frequencies and increased levels of activated B cells have been reported. Sensitized lymphocytes to brain extract were also described. Infectious diseases are frequent and may, sometimes, cause fatal outcomes. Increase of pro-inflamatory cytokines in serum and cerebrospinal fluid of epileptic patients were reported. Association with specific HLA antigens was described by several authors (HLA-DR7, HLA-A7, HLA-DRw52, and HLA-DR5). Auto-antibodies to brain antigens, of several natures (N-methyl-d-aspartate glutamate receptor, gangliosides, brain tissue extract, synaptic membrane, and others), were described in epileptic patients and in epileptic syndromes. Experimental epilepsy studies with anti-brain antibodies demonstrated that epileptiform discharges can be obtained, producing hyperexcitability leading to epilepsy. We speculate that in genetically prone individuals, previous cerebral lesions may sensitize immune system and trigger an autoimmune disease. Antibody to brain antigens may be responsible for impairment of T cell function, due to plasma inhibitory effect and also cause epilepsy in immature brains. © 2008 Bentham Science Publishers Ltd.
Keywords: Autoimmunity; Cell-mediated immunity; Humoral immunity; Lennox-Gastaut syndrome; Multifocal independent spikes; West syndrome; alpha interferon; antinuclear antibody; autoantibody; beta2 glycoprotein 1; brain antibody; brain antigen; cardiolipin; corticosteroid; corticotropin; cytokine; double stranded DNA; ganglioside; glutamate decarboxylase; glutamate receptor; glycoprotein gp 130; HLA A antigen; HLA A7 antigen; HLA antigen; HLA DR5 antigen; HLA DR7 antigen; immunoglobulin; interleukin 10; interleukin 1beta; interleukin 2; interleukin 6; interleukin 6 receptor; n methyl dextro aspartic acid receptor; phospholipid antibody; tumor necrosis factor alpha; unindexed drug; autoimmune disease; B lymphocyte; cellular immunity; clonal anergy; corticosteroid therapy; disease classification; epileptic discharge; hormonal therapy; human; hypsarrhythmia; immunotherapy; infantile spasm; Lennox Gastaut syndrome; nonhuman; onset age; remission; review; T lymphocyte; virus infection